Optimal Tube Bundle Arrangements in Side-Fired Methane Steam Reforming Furnaces - Engel, Sebastian; Liesche, Georg; Sundmacher, Kai; Janiga, Gábor; Thévenin, Dominique (Frontiers in Energy Research, 2020)
Steam methane reforming processes represent the economically most competitive processes for the production of synthesis gas and hydrogen despite their high energy costs. Although there is a strong need for highly resource-efficient production, literature on the optimal design of reformers remains scarce due to the inherently high complexity of these processes. This contribution addresses design aspects of reformers for the case study of a side-fired reformer. Based on a two-dimensional furnace representation heat transfer and the optimal tube bundle arrangement for a fixed furnace chamber are investigated using simulation-based parametric study with both a lean radiation-based model and a computational fluid dynamics model that enables the consideration of fuel efficiency. Radiative heat transfer prevails in the reformer on the furnace side and inter-tube distances of at least three diameters are optimal within the investigated design space. The line arrangement of reformer tubes is beneficial in terms of total heat transferred, fuel efficiency as well as the homogeneity of the tube surface temperatures. These findings pave the way for further studies such as three-dimensional design aspects.